Poverty and collective organization of the popular economy. The case of Bolivian migrant communities and their food production cooperative in Piedra Blanca, Córdoba - Avalle, Gerardo (2025)
Through the case of Piedra Blanca, a community on the outskirts of the city of Córdoba, Argentina, this study explores collective organization and cooperative production methods in peri-urban territories historically tied to social movements advocating for land rights. This case was selected due to three innovative features: the predominance of migrant-led food production, a predominantly female leadership, and the establishment of a cooperative as a subsistence project within the popular economy. An ethnographic methodology including interviews and field observations was employed. We found that the cooperative model, led by Bolivian migrants and Argentinean producers, offers a novel perspective for peri-urban rurality, with a strong emphasis on female leadership. This initiative, characterized by self-management and alternative commercialization networks, strengthens community resilience and provides a sustainable, socially viable alternative to traditional capitalist market structures.